Design and Implementation of a Culinary Tourism Promotion System for Ternate Using the FP-Growth Algorithm with the Waterfall Development Model - Muhammad Ridha Albaar; Rosihan Rosihan; Amal Khairan; Sadly Samsuddin; Haydar Qisyaam Sangadji; Destitha Almaqvira Bachmid (Institut Teknologi Gamalama, 2026)
Abstract: Based on this research, he application of the FP-Growth algorithm to identify culinary patterns. tourism promotion strategy in Ternate by knowing customer purchasing patterns in making promotional decisions so that it is targeted. The evaluation analysis indicates that applying FP-Growth is beneficial in devising effective promotional strategies by detecting frequently bought products. The detected patterns facilitate more efficient cross-selling and up-selling approaches, enabling businesses to react faster to marketplace shifts, enhance stock management efficiencies, and result in higher consumer satisfaction. The novelty of this study is the application of an extended FP-Growth framework attraction analysis not only used to determine interaction patterns but also directly incorporate association rules results in culinary tourism promotional strategy design according to Ternate regional characteristics.Keywords: FP-Growth, Promotion, Culinary Tourism, Data Analysis, Ternate Island